Pengaruh Penyesuaian Parameter Membership Function pada Sistem Kendali Robot Balancing Berbasis Fuzzy Logic - Santoso Santoso; Balok Hariadi; Ratna Hartayu; Reza Sarwo Widagdo; Wahyu Setyo Pambudi; M Ary Heryanto (Universitas Darul Ulum, 2024)
This research develops a balancing robot control system using a fuzzy logic approach, focusing on the adjustment of membership function parameters. The main components of the system include the ESP32 microcontroller, MPU6050 sensor for detecting tilt angle and angular velocity, and L298 motor driver for DC motor actuation. Triangular-shaped membership functions are implemented, and parameters a, b, and c are adjusted through simulation to enhance system performance. Evaluation results indicate an average settling time of 1.2 seconds, a maximum overshoot of 5%, and a steady-state error of less than 2 degrees. This adjustment successfully balances response speed and stability, providing important guidance for developers in designing a more optimal fuzzy logic control system. The research was conducted at the Electrical Engineering Laboratory of 17 August 1945 University (Untag) Surabaya from June to December 2023.